2013
DOI: 10.1523/jneurosci.0061-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Deep Sleep Stage inDrosophila

Abstract: Optogenetic upregulation of cyclic adenosine monophosphate during the day increases sleep intensity at night, whereas loss of function of a molecule involved in synaptic pruning, the fragile-X mental retardation protein, increases sleep intensity during the day. Our results show that sleep is not homogenous in insects, and suggest that waking behavior and the associated synaptic plasticity mechanisms determine the timing and intensity of deep sleep stages in Drosophila.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

32
278
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(310 citation statements)
references
References 46 publications
32
278
0
Order By: Relevance
“…We call this state of reduced arousal threshold "sleep," applying the same criteria used in previous studies that found that tethered flies, when asleep, have reduced neuronal activity (6, 7). We also show, again consistent with previous results (6), that sleep as defined in the current study is homeostatically regulated by the duration of previous wake. Thus, we conclude that the state of quiescence as defined in our experimental setup qualifies as sleep and not simply as rest.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We call this state of reduced arousal threshold "sleep," applying the same criteria used in previous studies that found that tethered flies, when asleep, have reduced neuronal activity (6, 7). We also show, again consistent with previous results (6), that sleep as defined in the current study is homeostatically regulated by the duration of previous wake. Thus, we conclude that the state of quiescence as defined in our experimental setup qualifies as sleep and not simply as rest.…”
Section: Discussionsupporting
confidence: 93%
“…The study concluded that neural activity in the sleeping fly brain, or at least in a central region spanning the MBs, resembles that seen in mammals in several brainstem cell groups including noradrenergic neurons, whose firing strongly declines or stops completely during sleep (9). A more recent study in tethered flies able to walk on an airsuspended ball also found that periods of immobility >5 min are associated with increased arousal thresholds and with "flat" LFPs (6). LFPs, however, reflect the activity of thousands of cells (10), and the use of modified stereotrodes to resolve single-unit activity in flies is still in its infancy (11).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…In Drosophila, although the majority of sleep occurs during the night, flies sleep a substantial amount during the day with males exhibiting more daytime sleep than females. 19,21,[70][71][72] Similarly, forager bees sleep primarily during the night [73][74][75] but also nap during the day. 76 In all other castes, sleep is distributed with approximately equal sleep occurring during the day and the night.…”
Section: Discussionmentioning
confidence: 99%
“…The MBs contain the neuronal population required to regulate normal sleep activity; overexpression of dFmr1 in the MBs reduced the prolonged sleep episodes of mutant flies (Bushey et al 2009). In another recent study, dFmr1 mutants showed a deeper night-like sleep phenotype during the day, which was regulated by two molecules, dFMRP and cAMP (van Alphen et al 2013). …”
Section: Dfmr1 Mutant Flies Have Abnormal Circadian Rhythmsmentioning
confidence: 92%